PENGARUH PARAMETER PROSES 3D PRINTING TERHADAP AKURASI DIMENSI FILAMENT PETG(Polyethylene terephthalate Gylacol) - Mawar Lestari; Subkhan Subkhan; Pristiansyah Pristiansyah (Politeknik Manufaktur Negeri Bangka Belitung, 2022)
3D printing is a manufacturing technology that is widely developed to make prototypes in accordance with the desired design, one of which is FDM (Fused Deposition Modeling). FDM technology is a printing technique used to print products using fibrous materials, some filaments that are often used in 3D printing including polylactic acid (PLA), acrylonitrile butadiene styrene (ABS), nylon, polyethylene terephthalate glycol (PETG) and polycarbonate (PC). This research aims to get the parameters that most affect the print of FDM 3D printing machines. In this study to print the filament test object used petg filament (Polyethylene terephthalate Gylacol) and using taguchi L27 OA method. The parameters used are Nozzel Temperature, Bed Temperature, Flowrate, Prin Speed, Layer Thiknes, Infill Overlap, Infill Density, and Infill Speed. The results of the study that has been done showed that the most influential parameters for the height of specimens are research no. 4 and 11 with a value of 19.99 while the lowest value is at number 26 with a value of 19.73 mm. And the most influential process parameters in a row are Nozzel Temperature (235°C), Bed Temperature (100°C), Infill Density (25%), Infill Overlap (10%), Layer Thickness (30mm), Printing Speed (40mm/s), Infill Speed (40mm/s), Flowrate (90%).